Tingkat Kewirausahaan Dan Kesuksesan Pada Usaha Kecil Menengah (UKM) - rahmawan, reza ardiansyah (Forum Bisnis Kewirausahaan, 2024)
The purpose of this paper is to determine the level or characteristics of entrepreneurship to achievesuccess in Small and Medium Enterprises (SMEs). SMEs play a role in providing employment and equity of income through business opportunities. Problems of SMEs on the difficulty of access to markets, information aid, finan-cial aid, and capital constraints. Facing such problems requires a strategy to achieve the success of Small and Medium Enterprises (SMEs) by improving the characteristics of entrepreneurs, characteristics of SMEs, and busi-ness performance.